TREN PENELITIAN PENGGUNAAN GEOGEBRA DI SEKOLAH DASAR PADA DATABASE SCOPUS: ANALISIS BIBLIOMETRIK - Zafrullah Zafrullah; Jumriani Sultan; Rizki Tika Ayuni; Yanti Kumala Sembiring; Annisa Fitriani (Jurnal Genta Mulia, 2024)
GeoGebra functions as a dynamic image media that allows students to interact with shifting points, measuring line segments and areas, providing direct experience for discovery activities and motivating students in learning mathematics, so that there is a lot of research using GeoGebra, especially in elementary education. This research focuses on analyzing publication trends related to the use of GeoGebra in basic education. Using RStudio and Vosviewer, researchers evaluated 70 Scopus documents with specified keywords. The analysis results revealed a significant increase in 2021, where 15 articles (21.43% of the total) were published, reaching the highest peak. 2022 also provided a high contribution with 13 articles (18.57%). Four main research focuses regarding GeoGebra in basic education were identified. Additionally, recent keyword analysis highlights “geogebrum” and “mathematics learning” as trends worth exploring further. This research provides insight into publication dynamics and current research trends in the use of GeoGebra, providing impetus for further exploration in the context of mathematics learning.